PEMANFAATAN APLIKASI QUIZZIZ DALAM PEMBELAJARAN FISIKA PADA MATERI FENOMENA KUANTUM - Ahmad Toni Pratama; Nana, Nana; Sulistyaningsih, Dwi (EduFisika: Jurnal Pendidikan Fisika, 2021)
This study aims to measure students' understanding of the concept of Â This study aims to measure students' conceptual understanding of quantum phenomena with the help of the quizizz application evaluation media. The research method uses descriptive methods. Learning evaluation using quizziz helps improve students' understanding of quantum phenomena. The understanding of students is 52% with an understanding level of understanding, 5% for understanding very understanding and 43% understanding enough. Learning evaluation using quizziz can be used by educators as an alternative ICT-based learning media to be utilized as much as possible to achieve learning objectives